PEMETAAN DAN PESEBARAN SPBU DI KOTA PADANG - Alexander Syam (STKIP Pesisir Selatan, 2016)
This study aims to determine Mapping General Fuel Filling stations (SPBU)in the city of Padang. Research methods used in this research is descriptive research method, the research subject is every SPBU in the city of Padang. Sampling is done by total sampling by finding the coordinates of every SPBU in the city of Padang. Data used primary data by conducting a survey of spaciousness direct and apply directly using GIS to describe the phenomena that exist in the field. Research is found that 1) a filling station in the city of Padang consists of 26 units. Located in 11 districts. 26 SPBU consists of 24 types Pasti Pas and 2 types Pertamina Way. 2) Distribution SPBU in the city of Padang wear elongated pattern, (Linear Concenration) that follow the main road due to SPBU for their effect on the road network. 3) The distance every SPBU in the city of Padang is different from one filling station to the other gas stations. It could even be said to be very close distance. As the SPBU to SPBU Didong Khatib Sulaiman PT. Karya Putra Muda Indonesia that did not reach 1 Km namely 732 meter.4) The location of SPBU in the city of Padang accidentally created two currents that flow in the left and right cross, and the current in opposite directions. To facilitate the accessibility of the SPBU itself.